ANALYSIS OF AIRSPACE STRUCTURE AND AIR NAVIGATION SERVICES AUTHORIZATION AT RAHADI OSMAN AIRPORT-KETAPANG - Rezika, Wida Yuliar; Wahyudi, Teddy; Irawan, Muhammad Zudhy (FSTPT Indonesia, 2015)
Air Traffic Controller at Rahadi Osman Airport Ketapang faces dilemma dealing with the obligations of Article 272, Law No. 1 of 2009 on Civil Aviation concerning the provision of navigation services and 429 concerning the sanctions to officials who do not have a navigation service certificate as if the conflicting views of airspace condition and navigation service authority there. This study aims to analyze the structure of controlled airspace and air navigation service authority with parameters : separation, cruising altitude distribution, efficiency and effectiveness of air navigation services. The results are the structure of Aerodrome Traffic Zone airspace and aerodrome control tower services are not able to accommodate the development of air traffic which impact to the violation of Article 429. Restructuring the airspace into the Control Zone with the authority of navigation services as an Approach Control to accommodate the operational needs and the law’s legality is the solution.